Sonic hedgehog signaling regulates a novel epithelial progenitor domain of the hindbrain choroid plexus - Huang, Xi (Company of Biologists, 2009)
Choroid plexuses (ChPs) are vascularized secretory organs involved in the regulation of brain homeostasis, and function as the blood-cerebrospinal fluid (CSF) barrier. Despite their crucial roles, there is limited understanding of the regulatory mechanism driving ChP development. Sonic hedgehog (Shh), a secreted signal crucial for embryonic development and cancer, is strongly expressed in the differentiated hindbrain ChP epithelium (hChPe). However, we identify a distinct epithelial domain in the hChP that does not express Shh, but displays Shh signaling. We find that this distinct Shh target field that adjoins a germinal zone, the lower rhombic lip (LRL), functions as a progenitor domain by contributing directly to the hChPe. By conditional Shh mutant analysis, we show that Shh signaling regulates hChPe progenitor proliferation and hChPe expansion through late embryonic development, starting around E12.5. Whereas previous studies show that direct contribution to the hChPe by the LRL ceases around E14, our findings reveal a novel tissue-autonomous role for Shh production and signaling in driving the continual growth and expansion of the hindbrain choroid plexus throughout development.